2012
DOI: 10.1007/s00586-012-2520-8
|View full text |Cite
|
Sign up to set email alerts
|

How is the trachea at risk of injury from pedicle screw insertion in proximal thoracic curve of adolescent idiopathic scoliosis patients?

Abstract: This CT-based study demonstrates that the FPT curve has a smaller safe zone with respect to tracheal injury during screw insertion. Spine surgeons should choose the appropriate screw length to avoid anterior wall perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Screw misplacement not only posed a significant threat to adjacent vital neurovascular or visceral structures but also decreased the pull-out strength of the screw, which consequently increased the possibility of instrumentation-related failures [ 19 , 20 ]. Such risks substantially increased in scoliosis patients with abnormal vertebral morphology and changed anatomic relationship between the vertebrae and surrounding vital structures [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Screw misplacement not only posed a significant threat to adjacent vital neurovascular or visceral structures but also decreased the pull-out strength of the screw, which consequently increased the possibility of instrumentation-related failures [ 19 , 20 ]. Such risks substantially increased in scoliosis patients with abnormal vertebral morphology and changed anatomic relationship between the vertebrae and surrounding vital structures [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had demonstrated that the morphology of proximal thoracic spine was smaller than that of distal thoracic spine and the smaller morphology of proximal thoracic spine was most likely associated with an increased risk of anterior cortical perforation [ 35 , 36 ]. Jiang’s study reported that the both esophagus and trachea were located in proximity to anterior cortex of proximal thoracic spine in AIS patients [ 21 , 22 ]. Spine surgeons should choose appropriate screw length to avoid anterior cortex perforation in TP region.…”
Section: Discussionmentioning
confidence: 99%
“…We encountered a significantly higher degree of thoracic correction postsurgery which corresponds with current literature which suggests that pedicle screws may just allow for the greatest degree of improvement in thoracic scoliosis than any other type of instrumentation. [1,8,11] In the article published by Suk et al, it was reported that pedicle screw-only surgery produced a 79.6% of thoracic curves and an 80.5% correction of lumbar curves and a study by Min et al revealed a mean correction in Cobb angle to be 68% when using pedicle screws only. [12] Meanwhile, hybrid systems used in a study by Liu et al reveal a 47% correction ratio.…”
Section: Discussionmentioning
confidence: 99%
“…We encountered a significantly higher degree of thoracic correction postsurgery which corresponds with current literature which suggests that pedicle screws may just allow for the greatest degree of improvement in thoracic scoliosis than any other type of instrumentation. [ 1 8 11 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation